The identification of Garcinia anomala (Clusiaceae) - Wang, Lei; Xie, Yifei; Zhang, Zhixiang (Phytotaxa, 2017)
The taxonomic status of Garcinia bracteata (Clusiaceae), a species endemic to China, has been questionable because its taxonomic traits are indistinct from Garcinia anomala and Garcinia propinqua. According to field investigations, careful examination of herbarium specimens, and statistical analysis, we assert that the traits previously used for distinguishing between G. bracteata, G. anomala and G. propinqua are unreliable for distinguishing these species. Therefore, G. bracteata and G. propinqua are being treated as synonyms of G. anomala. G. anomala is the earliest named species and thus has nomenclatural priority.